The Relationship Between Metabolic Syndrome and Urogenital Health Markers: A Cross-Sectional Study - Sönmez Topcu, Feyza; Özmerdiven, Gökhun; Demirel, Hüseyin Cihan (The European Research Journal, 2026)
Objective: Metabolic syndrome (MetS) is a cluster of metabolic abnormalities that increases cardiovascular risk and may adversely affect urogenital function, particularly erectile and prostate-related parameters. To evaluate the association between MetS and urogenital health markers, including erectile function, lower urinary tract symptoms, prostate volume, and internal iliac artery resistive index (RI).Methods: This cross-sectional study included 110 adult men without known cardiovascular, endocrine, oncological, or urological diseases evaluated at a hospital check-up clinic. Participants were grouped according to the presence of MetS. Erectile function (International Index of Erectile Function-5 [IIEF-5]), lower urinary tract symptoms (International Prostate Symptom Score [IPSS]), prostate volume, and internal iliac artery RI were assessed. Group comparisons were performed using non-parametric tests and the chi-square test, as appropriate.Results: Participants with MetS had significantly lower IIEF-5 scores and a higher prevalence of erectile dysfunction compared with MetS and without MetS (P=0.042). Although IPSS scores and prostate volume tended to be higher in the MetS group, these differences were not statistically significant (P>0.05). No significant differences were observed in internal iliac artery RI values between groups (P>0.05).Conclusion: MetS is significantly associated with erectile dysfunction and may contribute to impaired urogenital health. Internal iliac artery RI alone does not appear to be a sensitive early marker of urogenital vascular impairment.